Molecular candidates for early-stage flower-to-fruit transition in stenospermocarpic table grape (Vitis vinifera L.) inflorescences ascribed by differential transcriptome and metabolome profiles - Domingos, Sara (2018)
Flower-to-fruit transition depends of nutrient availability and regulation at the molecular level by sugarand hormone signalling crosstalk. However, in most species, the identities of fruit initiation regulatorsand their targets are largely unknown. To ascertain the main pathways involved in stenospermocarpictable grape fruit set, comprehensive transcriptional and metabolomic analyses were conducted specifi-cally targeting the early phase of this developmental stage in ‘Thompson Seedless’. The high-throughputanalyses performed disclosed the involvement of 496 differentially expressed genes and 28 differentlyaccumulated metabolites in the sampled inflorescences. Our data show broad transcriptome reprogram-ming of molecule transporters, globally down-regulating gene expression, and suggest that regulation ofsugar- and hormone-mediated pathways determines the downstream activation of berry development.The most affected gene was the SWEET14 sugar transporter. Hormone-related transcription changeswere observed associated with increased indole-3-acetic acid, stimulation of ethylene and gibberellinmetabolisms and cytokinin degradation, and regulation of MADS-box and AP2-like ethylene-responsivetranscription factor expression. Secondary metabolism, the most representative biological process attranscriptome level, was predominantly repressed. The results add to the knowledge of molecular eventsoccurring in grapevine inflorescence fruit set and provide a list of candidates, paving the way for geneticmanipulation aimed at model research and plant breeding